2013
DOI: 10.1080/11263504.2013.861540
|View full text |Cite
|
Sign up to set email alerts
|

Human trampling effects on Mediterranean coastal dune plants

Abstract: Coastal habitats are particularly vulnerable to recreational impacts because these environments are highly dynamic and continually change in response to biotic and abiotic factors. Sand dune communities are worldwide characterized by high levels of biodiversity, but are often affected by human-induced impacts as those caused by tourist trampling. To understand the effects of human frequentation, trampling, and other human-induced impacts, fencing experiments have been traditionally carried out on coastal dunes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…P. maritimum (sea or sand daffodil, sea or sand lily) grows naturally along the coastline of the Mediterranean region and blossoms during the hot and dry summer, at a time when simultaneously flowering plant taxa are scarce [3]. The expansion of its beautiful flowers coincides with the period of excessive tourism in coastal areas of the Mediterranean region; therefore, excess of floral sampling, tourist trampling, alteration, and dune erosion have seriously threatened populations of P. maritimum [4][5][6][7][8], which are expected to be further affected by sea-level rise and human-induced impacts [9,10]. Additionally, attention from the international scientific community has been given to the use of P. maritimum as a commercial, ornamental plant [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…P. maritimum (sea or sand daffodil, sea or sand lily) grows naturally along the coastline of the Mediterranean region and blossoms during the hot and dry summer, at a time when simultaneously flowering plant taxa are scarce [3]. The expansion of its beautiful flowers coincides with the period of excessive tourism in coastal areas of the Mediterranean region; therefore, excess of floral sampling, tourist trampling, alteration, and dune erosion have seriously threatened populations of P. maritimum [4][5][6][7][8], which are expected to be further affected by sea-level rise and human-induced impacts [9,10]. Additionally, attention from the international scientific community has been given to the use of P. maritimum as a commercial, ornamental plant [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of trampling on shores has been extensively studied (e.g., Farris et al, 2013;Davenport and Davenport, 2006;Beauchamp and Gowing, 1982) and it is associated with economic activities such as tourism and commercial harvesting in coastal areas (Sarmento and Santos, 2012;Schlacher and Thompson, 2012;Veloso et al, 2008). It has been reported in literature that human trampling and shellfish harvesting, clearly have negative effects on the fauna of sandy beaches (e.g., Farris et al, 2013;Sheehan et al, 2010;Moffett et al, 1998) and this is considered to be a major cause of biodiversity loss in protected areas (Andersen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in literature that human trampling and shellfish harvesting, clearly have negative effects on the fauna of sandy beaches (e.g., Farris et al, 2013;Sheehan et al, 2010;Moffett et al, 1998) and this is considered to be a major cause of biodiversity loss in protected areas (Andersen, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…As a model species we chose A. sardoa, a narrow endemic plant that grows in a limited area where the touristic impact is very high both in habitat loss and in human trampling (Farris et al, 2013). Genetic data showed that this species has low levels of genetic variation due to bottleneck events caused by loss of habitat and natural stochastic factors (Bacchetta et al, 2008;Coppi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%